2017
DOI: 10.1111/acps.12733
|View full text |Cite
|
Sign up to set email alerts
|

The ‘cognitive footprint’ of psychiatric and neurological conditions: cross‐sectional study in the UK Biobank cohort

Abstract: ObjectiveWe aimed to quantify the prevalence of cognitive impairment in adults with a history of mood disorder, schizophrenia, multiple sclerosis or Parkinson's disease, within a large general population cohort.MethodCross‐sectional study using UK Biobank data (n = 502 642). Psychiatric and neurological exposure status was ascertained via self‐reported diagnoses, hospital records and questionnaires. Impairment on reasoning, reaction time and memory tests was defined with reference to a single unexposed compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…On the other hand, there was no significant difference between the groups in the visual memory scores as shown in Table 1. This matched the study in a UK Biobank data which investigated the cognitive functions footprint of different psychiatric and neurological disorders in 2017 [17]. It revealed that 1.89-3.92% of the examined sample (n = 502,642) who were diagnosed as schizophrenic suffered from cognitive dysfunction in reasoning, pair matching, numeric memory, and reaction time [17].…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, there was no significant difference between the groups in the visual memory scores as shown in Table 1. This matched the study in a UK Biobank data which investigated the cognitive functions footprint of different psychiatric and neurological disorders in 2017 [17]. It revealed that 1.89-3.92% of the examined sample (n = 502,642) who were diagnosed as schizophrenic suffered from cognitive dysfunction in reasoning, pair matching, numeric memory, and reaction time [17].…”
Section: Discussionsupporting
confidence: 73%
“…Several studies have shown that BD patients may exhibit cognitive decline during the disease course. However, these results vary with regard to the cognitive domains affected, as well as the associated risk factors (Arts et al, 2008;Bora et al, 2009;Cullen et al, 2017;Gildengers et al, 2007). The number of manic episodes seems to be the clinical marker most strongly associated with neuroprogression in BD, as described in recent reviews (Passos et al, 2016).…”
Section: Clinical Symptoms Of Bipolar Disorder Relevant To Neurology mentioning
confidence: 96%
“…Although cognitive impairments are present in various psychiatric disorders, they can be especially prominent in BD (Cullen et al, 2017;Vohringer et al, 2013). The trajectory of BD can be highly variable, and progressive worsening of cognitive functions can occur in a subgroup of these patients (Burdick et al, 2015;Van Rheenen et al, 2017).…”
Section: Clinical Symptoms Of Bipolar Disorder Relevant To Neurology mentioning
confidence: 99%
“…It contains information about dates of admission/release/operation, diagnosis codes, in ICD10 (or ICD9 if prior to 2000), as well as operations & procedure (OPCS) codes when applicable. The aim of researchers using HES data is to find instances of specific diseases or incidents and link them to the subject's lifestyle, genomic profile or imaging results (ex: Cullen, B. et al, 2017;Celis-Morales, C.A. et al, 2017).…”
Section: Hes Recordsmentioning
confidence: 99%